Eklesiologi Ibu: Merangkul dan Memulihkan Trauma Pelaku [Kekerasan dalam Sejarah] G30s/PKI - Yoggy Hermondi Manu; Costantinus Ponsius Yogie Mofun; Daniel L Sindang (Program Pascasarjana UKIM, 2023)
The historical memory of the G30s/PKI creates collective social trauma and revives feelings of hatred and revenge towards the G30s/PKI perpetrators. The families of the perpetrators experienced bad stigma and discrimination, resulting in a burden and historical trauma. This article aims to examine the process of recovering from the historical burdens and trauma experienced by the families of the perpetrators. We offer the concept of the church as a mother who embraces and heals the trauma of the families of G30s/PKI perpetrators. This article uses qualitative methods with a historical analysis and trauma recovery approach, which uncovers and recovers the traumatic history of the families of the G30s/PKI perpetrators. This research found that the trauma healing process is carried out through three stages, namely stabilizing safety, remembering and mourning, and reconnection. The ecclesiology of the church as a mother emphasizes the presence of the church to hear the voices of pain, and accept, guide, and protect the families of G30s/PKI perpetrators like a mother embracing her children. We discuss these findings in three main parts, namely the stages of trauma recovery, the ecclesiology of the church as mother according to John Calvin, and the role of maternal ecclesiology, which embraces the perpetrator's family in the experience of discrimination and historical trauma.